Pengaruh Video Virtual Tour 360° Pantai Kuta Terhadap Respon Emosional Audiens - Paramartha, I Putu Adi Surya; Julianto, I Nyoman Larry; Mudra, I Wayan (Universitas Komputer Indonesia, 2023)
The presence of a 360° virtual tour video as a medium with a new format in Indonesia has the potential to be an alternative way of traveling as well as a medium for promoting a tourist attraction with a new format. The unique experience that 360° videos offer can influence the emotional response of the viewer which in turn can potentially influence the viewer's actions. The purpose of this research is to determine the emotional response of respondents when watching a 360° virtual tour video about Kuta Beach. This qualitative research uses emotional design theory approach in the analysis process. Data collection techniques are carried out using documentation and questionnaire methods. The results of this research indicate that respondents tend to feel more positive emotion than negative emotions when watching a 360° virtual tour video about Kuta Beach. Most of the positive emotion are caused by the visual scene generated based on a particular camera placement, especially when there was movement of the camera. Meanwhile, the negative emotional response, especially the boredom type, was caused by the placement of the camera which was only stationary in one place. In addition, it was also found that personal factors such as personality and culture can also affect emotional responses when watching 360° videos.